Relationship Between Leadership Styles of Sports Administrators and Orgranisational Development in Ilorin Metropolis, Nigeria - Issa Yaqub Ajeigbe; Abdulraheem Yunus Owolabi; Semiu Alasinrin (INDONESIAN JOURNAL OF SPORT MANAGEMENT, 2021)
Leadership styles remain very pertinent in the effective performance of an organization. Without good leadership ability to coordinate the staff and the activities in an organization may be hampered thereby affecting the overall development of such organization. Leadership is an important determinant in the effective functioning of an organization. The research employs descriptive survey design of correlation type which is very important as the study tries to find out the relationship between leadership styles of sports administrators and organization performance in Ilorin. Two research questions and three operational hypotheses were formulated for the study. The target populations for the study are 62 sports personnel in the sports council Ilorin which comprised of Director of Sports, Stadium manager, organizing secretaries and coaches of the existing 20 sports in the Kwara State Sports Council. No sample is selected as the researcher made use of all the sports personnel as respondents for the study. Researcher questionnaire designed in a modified four points likert rating scale was used to collect data from the respondents which was validated by a Professor of sports management, Kwara State University, Malete and a season sports administrator, ministry of youth and sports, Abuja and tested for reliability using split half method and Cronbach alpha was used to determine the result with a coefficient of 0.80 obtained. Inferential statistic of multiple regressions was used to test the null hypotheses formulated at 0.05 level of significance. The findings reveal that leadership styles of sports administrators have significant relationship with organization performance, each leadership style has significant contribution to organization performance and all the leadership styles significantly contributed to organization performance. Among the recommendations suggested include: Sports administrators must be able to employ variety of leadership style is the best among others. Keywords: Leadership styles, sports Administrator and organization performance